The Theory of Financial Intermediation: An Essay On What It Does (Not) Explain - Bert Scholtens; Dick van Wensveen (SUERF - The European Money and Finance Forum, 2003)
This essay reflects upon the relationship between the current theory of financial intermediation and real-world practice. Our critical analysis of this theory leads to several building blocks of a new theory of financial intermediation. Current financial intermediation theory builds on the notion that intermediaries serve to reduce transaction costs and informational asymmetries. As developments in information technology, deregulation, deepening of financial markets, etc. tend to reduce transaction costs and informational asymmetries, financial intermediation theory shall come to the conclusion that intermediation becomes useless. This contrasts with the practitioner's view of financial intermediation as a value-creating economic process. It also conflicts with the continuing and increasing economic importance of financial intermediaries. From this paradox, we conclude that current financial intermediation theory fails to provide a satisfactory understanding of the existence of financial intermediaries. We present building blocks for a theory of financial intermediation that aims at understanding and explaining the existence and the behavior of real-life financial intermediaries. When information asymmetries are not the driving force behind intermediation activity and their elimination is not the commercial motive for financial intermediaries, the question arises which paradigm, as an alternative, could better express the essence of the intermediation process. In our opinion, the concept of value creation in the context of the value chain might serve that purpose. And, in our opinion, it is risk and risk management that drives this value creation. The absorption of risk is the central function of both banking and insurance. The risk function bridges a mismatch between the supply of savings and the demand for investments as savers are on average more risk averse than real investors. Risk, that means maturity risk, counterparty risk, market risk (interest rate and stock prices), life expectancy, income expectancy risk etc., is the core business of the financial industry. Financial intermediaries can absorb risk on the scale required by the market because their scale permits a sufficiently diversified portfolio of investments needed to offer the security required by savers and policyholders. Financial intermediaries are not just agents who screen and monitor on behalf of savers. They are active counterparts themselves offering a specific product that cannot be offered by individual investors to savers, namely cover for risk. They use their reputation and their balance sheet and off-balance sheet items, rather than their very limited own funds, to act as such counterparts.
Keywords: E50; G20; G10; L20; O16; 330; Financial Intermediation; Corporate Finance; Assymetric Information; Economic Development; Risk Management; Value Creation; Risk Transformation; Finanzintermediation; Theorie